Evaluation of Antiangiogenic Potential of Ethanolic Extract of Bauhinia variegata Leaves in Mice - Kathole, Namrata S; Karande, Vikas V; Ghumare, Babasaheb C; Mote, Chandrashekhar S; Lonkar, Vijaysinh D; Jadhav, Samir N; Bachapalle, Pooja P (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was planned to evaluate the antiangiogenic potential of ethanolic extract of Bauhinia variegata using the sponge implantation method in mice. Swiss albino adult male mice (n=30) weighing 18-22 g were divided into three groups comprising of ten animals in each. Groups I, II, and III were used as negative control, positive (SU5416) control, and treatment (extract of Bauhinia variegata) groups, respectively. Sponges were implanted subcutaneously and the mice were sacrificed after 14th day. The implanted sponges were then segregated and processed for haemoglobin concentration, vascular endothelial growth factor (VEGF) estimation, and histopathological evaluation. In treatment groups I to III, the mean (±SE) haemoglobin content was found to be 1.919±0.048, 0.410±0.049, and 1.604±0.101 µg/mg weight of sponge, VEGF values 2.462±0.181, 0.529±0.044, and 1.609±0.069 pg/mg weight of sponge, and the mean vessels density (±SE) per field (microscopically under 40x) was 14.9±1.25, 1.3±0.3, and 10.6±0.92, respectively. The extract of Bauhinia variegata was found to have inhibitory potential on hemoglobin concentration, VEGF concentration, and mean vascular density.
Keywords: Angiogenesis; Bauhinia variegata; VEGF; MVD; Sponge implant